Pendekatan Bayani, Burhani dan Irfani dalam Pembentukan Mental Spiritual Siswa MTs N 2 Tanggamus Lampung - M. Ibnu Naufal Maskuri (Pendidikan Guru Madrasah Ibtidaiyah STIT Palapa Nusantara, 2022)
At present, there are many educated people who are in the spotlight due to their own actions, such as the occurrence of violence, as well as their behavior that is not good, far from social behavior and from a religious point of view as it should be. This research was conducted to determine the bayani, burhani and irfani approaches in the formation of mental and spiritual students of MTS N 2 Tanggamus Lampung. Mental-spiritual is a pattern of coaching in the process of bringing individuals closer to the creator, namely God. Spiritual mental intelligence includes aspects of attitudes, actions, and behavior that reflect individuals in accordance with the religious teachings they believe in. In this study, the researcher used a descriptive qualitative approach, by collecting data through observation, interviews and phenomenology. The results of this research are that the first bayani approach in the formation of students' mental and spiritual is carried out with a religious text, through the subjects of Akidah Akhlak, Fiqh, Arabic, Islamic Cultural History and Al-Quran Hadith. Both burhani approaches, in the formation of students' mental and spiritual spirituality, are carried out by giving examples of positive behavior of a teacher to students by prioritizing 5S, motivating students to like reading books, giving small gifts to students when they can answer questions, and studying general knowledge such as science, social studies, Arts, Physical Education and Lampung Language, which can make students and students fully social beings. Furthermore, the three irfani approaches, in the formation of students' mental spirituality, are applied by means of religious activities, performing congregational duha prayers, muhadhoroh, recitations, and spiritual activities.